(untitled) (Himalayan Review, 2024)
Land use land cover (LULC) area has been changing for many decades in the Kailali district but has little been researched. The study aims to examine the spatial and temporal changes of LULC from 1978 to 2021, carrying out major driving factors of forest cover change regarding forest encroachment and abandonment. The researcher employed a mixed-method approach to accomplish this study. Field observation, household survey with 45 participants, Key Informant Interviews (KII) with three participants, and five Focus Group Discussions (FGD) were used as research tools to collect the data. Moreover, the researcher used books, journal articles, official reports, and related previous empirical studies as secondary data [Land Resource Mapping Project (LRMP) data were used to screen LULC status of 1978 and 1990, and digitization on Google Earth Pro to prepare LULC data for 2000 and 2021]. The findings of the study revealed that the forest cover area of the Kailali district was in a decreasing trend [ for instance in 1978 the area of forest cover was 75.38%, in 1990 it was 66.51% in 2000, and was 65% in 2021]. In contrast to forest cover, the agricultural [settlements and infrastructures] land area was on an increasing trend which was followed by 21.77%, 30.28%, 31.75%, and 32.25% in each period. The study also found that the changing rate of forest cover and the agricultural land have been decreasing. Further, the research found the major drivers of forest cover change were encroachment and agricultural land abandonment. In addition, population growth, migration, poverty, development activities, natural hazards, resettlement, public utilities, weak implications of policy, and illegal activities were also the major causes of forest cover change. The research implies that both forest encroachment and land abandonment should be controlled, and are to be considered by the stakeholders.